ANAK JALANAN DI KOTA KENDARI MENUJU KOTA LAYAK ANAK - Masdin Masdin (Institut Agama Islam Negeri Kendari, 2017)
Street children in Kendari are as same as other children in the universe who have the right to get education and play around. This study aims to analyze the street children phenomenon within the framework child-friendly-city (KLA). Some of the street children in Kendari attend formal school and some of them take informal one, especially in one of street children communities in Kendari; called KOJAK, or most of them do not attend any educational institutions since they encounter financial problem. They make a living in the streets to help their parents’ economy condition. Some of them are staying with their parents, but others have no place to live and stay on the road. They work as street musician to fulfill their needs. Recently, there is no special education for street children facilitated by the government. Under KLA framework, the children need to obtain education because it is their right to pursue their dreams in the future. The city government has not facilitated education for street children, and the street children who attend school are initiatives from parents or non-governmental organizations.